Thrombin-activatable fibrinolysis inhibitor levels in patients with non-small-cell lung cancer - (:unkn) unknown (CIG MEDIA GROUP, LP, 2008)
BACKGROUND: An increased incidence of thromboembolic events has been described in patients with cancer. Cancer cells are attributed with producing procoagulant substances such as cysteine protease and tissue factor to activate factor X and factor VII, respectively. However, there are limited data on the pathogenesis behind this hypercoagulability state, and the thrombin generation, fibrinolytic system, and coagulation inhibition system during cancer are largely obscure. In this study, we investigated the changes of different steps of coagulation pathway in patients with non-small-cell lung cancer (NSCLC) and compared the data with those of healthy controls. PATIENTS AND METHODS: Forty-four patients with NSCLC and 36 age-matched controls were recruited for this study. Prothrombin fragment 1 + 2 (F 1 + 2) were used as a marker of thrombin generation; thrombin-activatable fibrinolysis inhibitor (TAFI) immunologic activity level was measured for inhibition of the fibrinolytic system, and tissue factor pathway inhibitor (TFPI) activity was assessed for the coagulation inhibition system. In the patient group, the relationships between TAFI activity levels and patient parameters (age, sex, body mass index [BMI], histopathology, and stage) were evaluated. RESULTS: The TAFI activity, F I + 2 levels, and TFPI activity were significantly higher in patients with lung cancer than in subjects in the control group (P <.05; P <.0001; and P <.0001; respectively). However, there were no statistically significant associations between TAFI activity levels and patient age, sex, BMI, histopathology, or stage of disease (P >.05). CONCLUSION: In this study, it was clearly shown that patients with lung cancer have hypercoagulable states and that the pathogenesis of thrombotic events in these patients is multifactorial. Increased TFPI is a reflection of thrombin activity in this patient group. Confirmatory studies with larger patient groups should be performed in this population.
Keywords: carboxypeptidase U; plasminogen activator inhibitor-1; prothrombin fragment; tissue factor pathway inhibitor; venous thromboembolism; ACUTE PROMYELOCYTIC LEUKEMIA; PLASMA TAFI; COAGULATION; PATHWAY